Analysis Of The Use Of Digital Technology In Insurance Premium Management - Lutfiah Nur, Dara; Nasution, Muhammad Irwan Padli (Indonesian Scientific Publication, 2024)
An insurance claim is a claim from the insured party based on a contractual agreement with the insurance company which guarantees payment of compensation as long as the insured party pays the premium. In other words, submitting an insurance claim is an official request from the insurer to request payment as regulated by the terms of the insurance policy. Currently, the use of insurance is increasingly popular with the public, almost all risks can be covered by insurance, and insurance has become an important factor for society. Indonesia, Community and Company trust. Therefore, increasing the efficiency of insurance companies must support public confidence in insurance. Civil Code, and National Law 2 of 1992 concerning Insurance Services, according to Law no. 40 of 2014 concerning insurance services, providing legal protection for policy holders. Law 8 of 1999 concerning Consumer Protection explains the authority, duties and prohibited actions of insurance companies as business actors as well as resolving insurance disputes and claims. Although the relationship between policy holders and insurance companies falls under civil law, the consumer protection law provides criminal sanctions for parties who violate the Consumer Protection Law, including insurance companies.